2004
DOI: 10.1542/peds.2004-1232
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Controlled Trial of Slow Versus Rapid Feeding Volume Advancement in Preterm Infants

Abstract: Among infants between 1000 and 2000 g at birth, starting and advancing feedings at 30 mL/kg per day seems to be a safe practice and results in fewer days to reach full-volume feedings than using 20 mL/kg per day. This intervention also leads to faster weight gain and fewer days of intravenous fluids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
1
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 20 publications
5
67
1
4
Order By: Relevance
“…feedings, using feeding guidelines, have been implemented and these too have been shown to improve weight gain. [13][14][15][16][17][18] We recognize that our new weight grid does not display 'ideal' weight changes, but it displays actual changes, using a large cohort of heterogeneous low birth weight (LBW) NICU patients in four different hospitals. The lack of initial weight loss we observed among the smallest neonates was not seen in the previous growth grids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…feedings, using feeding guidelines, have been implemented and these too have been shown to improve weight gain. [13][14][15][16][17][18] We recognize that our new weight grid does not display 'ideal' weight changes, but it displays actual changes, using a large cohort of heterogeneous low birth weight (LBW) NICU patients in four different hospitals. The lack of initial weight loss we observed among the smallest neonates was not seen in the previous growth grids.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] On the basis of these, we hypothesized that NICU patients cared for currently have more rapid weight gain than are displayed on the commonly used postnatal grids. [2][3][4][5] To test this we collected, from electronic records, all daily weights of all patients with birth weights 400-2600 g, born during a 30-month period, January 1, 2003-June 30, 2005, cared for in any the NICU's of the Intermountain Health Care (IHC) System.…”
Section: Introductionmentioning
confidence: 99%
“…Four prior randomized trials found that more rapidly advancing feeding regimens in premature infants resulted in more rapid attainment of birth weight and shorter time to full feedings without increasing the incidence of NEC. [21][22][23][24] A case-control study found that infants who developed sepsis had feedings initiated later than infants who did not, but that infants who developed NEC were fed at the same age (3 to 4 days) as infants who did not. 25 In contrast, a randomized trial, comparing rapid vs slow advancement of feeding was discontinued early because of an increase in NEC in the rapid advancing group.…”
Section: Feeding Issuesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Little evidence is available to guide these decisions, especially about feeding interval. Several small studies and a systematic review suggest that intermittent bolus feedingsFcompared with continuous feedingsFimprove feeding tolerance and growth in VLBW infants.…”
Section: Introductionmentioning
confidence: 99%